Analysis of the Acceleration of Tower Project Activities using the What/If Method - Juniarti, Risma Sari; Bangkara, Anaconda; Wisaksono, Anggoro (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
In the construction of the Pegadaian Tower project, the delays experienced were evidenced by the project implementation not being in accordance with the plans that had been designed before the construction process began. The project planning made by the contractor is planned for the topping off process or final floor casting of the superstructure construction phase to be carried out in September 2022 or in the 18th month of the total 25 months of work on this project. Efforts made to adjust the implementation of the plan were to accelerate this project, where the acceleration was carried out using the What/If method by adding working hours (overtime) and the number of workers at the research object who worked on the Mezzanine floor to the 5th floor at the superstructure stage. Apart from the What/If method as an acceleration solution, initial efforts were made by evaluating the project schedule using the Precedence Diagramming Method (DPM) network planning method with the help of Microsoft Project software. The analysis carried out resulted in good acceleration where the acceleration analysis using the What/If method can speed up the completion of superstructure construction so that it can help achieve the topping off target in September according to what has been planned in the schedule. Meanwhile, adding labor and working time to these three important activities can speed up the duration of the project so that the project avoids contract loss penalties with the owner.